New preparations of hematopoietic growth factors - Świeboda-Sadlej, Anna (Contemporary Oncology/Współczesna Onkologia, 2004)
Cancer chemotherapy is associated with a high risk of complications due to neutropenia and thrombocytopenia. Over the past decade, several new preparations of hematopoietic growth factors have been developed. Some of them are reviewed in this paper. Pegfilgrastim (Neulasta, Amgen) is a novel pegylated form of filgrastim. Pegfilgrastim has a longer half-life than filgrastim, which allows for once-per-chemotherapy cycle frequency of administration and improves the patient’s quality of life. Its safety profile and tolerability are similar to those of filgrastim. Currently, rhIL-11 (Neulasta, Amgen) is the only cytokine licensed in the USA for treatment of chemotherapy-induced thrombocytopenia. rhIL-11 reduces the duration of thrombocytopenia and the need for platelet transfusions. c-MPL ligands such as recombinant human thrombopoietin (rhTpo) and pegylated recombinant human megakaryocyte growth and development factor (PEG-rHuMGDF) offer important promise for the treatment of thrombocytopenia. However, the development of neutralizing antibodies and clinically significant thrombocytopenia in some patients and normal donors is responsible for the delay in their commercial availability. Other hematopoietic growth factors, such as Steel factor (SLF), a fusion protein of Tpo and IL-3 and peptides that are hematopoietic growth factor mimetics presently evaluated for their clinical use are also mentioned in this review.